2022
DOI: 10.1055/s-0042-1756692
|View full text |Cite
|
Sign up to set email alerts
|

Microshear Bond Strength of Bioactive Materials to Dentin and Resin Composite

Abstract: Objectives The aim of this study was to comparatively evaluate microshear bond strength (μSBS) of bioactive ionic resin composite and resin-modified glass ionomer liner (RMGI) to dentin and resin composite. Materials and Methods The enamel of 11 posterior molar teeth was removed to expose dentin and then placed in acrylic blocks. Each specimen received three microcylindrical Tygon tubes filled with bioactive ionic resin composite (Activa Bioactive base/liner (Pulpdent, MA, USA)), RMGI (Riva light cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(42 reference statements)
1
2
0
Order By: Relevance
“…Moreover, the proper restorative techniques and the adequate marginal seal of the restorations prevented the bacterial penetration. The antibacterial and remineralizing ability of Activa Bioactive and Riva Light Cure liners had a crucial role in caries prevention, as well both lining materials showed high bond strength to dentin and resin composite which might prevent secondary caries and microleakage as reported by a previous laboratory study 50 . This finding was in agreement with a clinical trial 56 which stated that both Activa Bioactive and RMGI scored 100% success after 1 year regarding the recurrence of decay.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Moreover, the proper restorative techniques and the adequate marginal seal of the restorations prevented the bacterial penetration. The antibacterial and remineralizing ability of Activa Bioactive and Riva Light Cure liners had a crucial role in caries prevention, as well both lining materials showed high bond strength to dentin and resin composite which might prevent secondary caries and microleakage as reported by a previous laboratory study 50 . This finding was in agreement with a clinical trial 56 which stated that both Activa Bioactive and RMGI scored 100% success after 1 year regarding the recurrence of decay.…”
Section: Discussionsupporting
confidence: 51%
“…This could be attributed to the active ionic resin matrix and shock absorbing rubberized fillers in Activa Bioactive liner which bond chemically to tooth structure and provide sealing against bacterial leakage and thus, reducing sensitivity. Moreover, Activa Bioactive has the ability to release and recharge calcium, phosphate, and fluoride ions provoking the mineral apatite formation and remineralization 50 . This was supported by Hirani et al 51 who reported that there was no postoperative hypersensitivity related to Activa Bioactive material.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports in the literature about the mechanical properties of these newly launched materials [ 24 , 25 , 26 , 29 , 30 ]. In addition, previous studies reported the effect of treatment with CHX and SDF on the bonding of resin composite to dentin [ 16 , 20 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%